Universality without Domain: The Ontology of Hermeneutical Practice. Issue 48 (3rd July 2017) - Chiurazzi, Gaetano
ABSTRACT: Hermeneutic rationality arises from the idea that experience is a cumulative process, in which differences are not eliminated (as it happens in the abstractive process of science) but preserved. The universality which derives from this process is an "intensional universality", which follows a law of direct (and not inverse) proportionality between extension and intension: the more an educated individual enriches her experiences, the more she is able to universalize her understanding of others. Experience is then inevitably open and never closed, that is, free for other experiences. If we use the word "domain" to describe the condition of a closed and predetermined system or ontology, the entities of which are pre-assumed, we can therefore call this open universality a "universality without domain". This description of hermeneutical experience leads to a question about its logical and ontological presuppositions. In the second part of the paper I refer to a particular practice which is central for hermeneutical theory in order to show how I understand these presuppositions: the practice of translation. In translation we experience the impossibility of rendering completely the sense of the source language in a target language, that is, we experience a difference which cannot be suppressed. I compare this experience to the discovery of the incommensurable magnitudes in ancient Greek mathematics, a discovery that shook Parmenidean and Pythagorean ontology: in my opinion, philosophical hermeneutics more or less implicitly develops the consequences of this incredible discovery, which marks the passage to a differential, comparative and integrative rationality and ontology.